Building the Clinical Bridge: An Australian Success - Marianne Wallis; Wendy Chaboyer (Hindawi Limited, 2012)
Nursing effectiveness science includes primary, secondary, and translational, clinically focused research activities which aim to improve patient or client outcomes. It is imperative, for the successful conduct of a program of nursing effectiveness science, that a clinical bridge is established between academic and healthcare service facilities. An Australian example of the development of a robust clinical bridge through the use of jointly funded positions at the professorial level is outlined. In addition, an analysis of the practical application of Lewin's model of change management and the contribution of both servant and transformational leadership styles to the bridge building process is provided.